Społeczne (re)konstrukcje zawodu inżyniera w kontekście rosnącego udziału kobiet w tradycyjnie męskich obszarach zawodowych - Szymczak, Emilia (Studia Edukacyjne, 2020)
Nowadays, women more often want to pursue their professional aspirations in areas related to engineering. This is evidenced by statistical reports related to the growing participation of women in the polytechnic studies, as well as a growing proportion of young women working as engineer. It is inseparably connected with the contemporary changes and discoveries in technology, thanks to which the society - the remaining phase of permanent development - stands in the need for a greater number of specialists and workers in order to meet increasing, as well as constantly changing needs of social, economic and market conditions. This article is a (re)construction of professional functioning of women in engineering with special emphasis on factors which may provide an incentive to undertake this type of work; analysis of the same professional environment in the context of the problem of social inequality, as well as the phenomenon of masculinization of women in engineering.